FAKTOR YANG MEMENGARUHI UPAYA PENINGKATAN INDEKS PEMBANGUNAN MANUSIA (IPM): KASUS IPM PROVINSI YANG MASIH DIBAWAH IPM NASIONAL - Kharisma, Bayu; Wardhana, Adhitya; Zidan Fauzy, M (Buletin Studi Ekonomi; VOLUME.29.NO.02.TAHUN.2024DO - 10.24843/BSE.2024.v29.i02.p03, 2024)
Indonesia's Human Development Index (HDI) is a tool for assessing the quality of human resources, but some provinces still fall short in the education dimension, which is crucial for improving the HDI value. The education index is determined by variables like Mean Years of Schooling (MYS) and Expected Years of Schooling (EYS). This study aims to analyze the factors influencing the education dimension through MYS and EYS, using a descriptive analysis with a panel data model. The research sample consists of 120 observations from 24 provinces from 2017 to 2021, with provinces with an HDI value below the national HDI. The fixed effects method is used to analyze the relationship between independent and dependent variables. The provinces included in this study are those with an HDI value below the national HDI. Based on the Chow test and Hausman test results, this study uses the fixed effects method to analyze the relationship between independent and dependent variables. The findings suggest that government expenditure on education is the most significant variable affecting both MYS and EYS.